Management of chronic pelvic pain : a practical manual - 4 0 16; Hibner, Michael; 5 (Cambridge, United Kingdom ;;New York, NY : Cambridge University Press, 2020)
Pelvic pain is much more common condition than perceived by medical and general community. Because it affects the most private aspects of human life such as sexuality and reproduction patients are not willing to discuss it with their family, friends and loved ones. Medical providers are also very likely to dismiss the symptoms and blame it on psychological or psychiatric condition. Chronic pelvic pain is real, it is common, it is almost always due to some identifiable disease or injury. Patients with pelvic pain need to be heard and treated with dignity and respect and they majority of them can be helped--
Introduction to Chronic Pelvic Pain / Michael Hibner & Ashley Gubbles -- Neurobiological Basis of Pelvic Pain / Ashley Gubbels -- History and evaluation of patients with chronic pelvic pain / Nita Desai & Mario Castellanos -- Psychological assesment of a female patient with chronic pelvic pain / Dean Tripp, Katherine Fretz & Curtis Nickel -- Musculoskeletal Assessment for Patients with Pelvic Pain / Lauren Hill & Karen Brandon -- Pharmacological management of patients with pelvic pain / Diana Atashroo & Richard Cockrum -- Evidence for surgery in patients with pelvic pain / Nita Desai & Anna Reinert -- Pelvic Pain Arising from Endometriosis / Mark Dassel -- Pelvic pain arising from interstitial cystitis or Bladder Pain Syndrome (as is mentioned in the chapter) / Katherine De Souza & Charles Butrick -- Pelvic pain arising from pelvic congestion syndrome / Nita Desai -- Pelvic pain arising from irritable bowel syndrome / Maryam Kashi & Seetha Lakshmanan -- Vulvodynia / Georgine Lamvu & Jorge Carrillo -- Pelvic pain arising from adhesive disease / Joseph Maurice & Sheena Galhotra -- Pelvic pain arising from ovarian remnant syndrome / Mohammad Islam & Javier Magrina -- Pudendal neuralgia / Mario Castellanos & Michael Hibner -- Other peripheral pelvic neuralgias / Katherine DeSouza & Mario Castellanos -- Chronic pelvic pain after gynecologic surgery / Anna Reinert & Michael Hibner -- Pain arising from pelvic mesh implants / Ashley Gubbels & Michael Hibner -- Treatment of sexual dysfunction arising from pelvic pain / Debra Wickman -- Physical therapy interventions for musculoskeletal impairmentss in pelvic pain / Lauren Hill -- Pelvic pain: if all else fails / Michael Hibner.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; Treatment.;Treatment. -- Pelvic pain;Chronic pain -- 20; 20; 2